Quality of Environmental Impact Assessment Reports for Lodge Developments in Protected Areas: The Okavango Delta Case, Botswana - LEEPILE, Leungo Boikanyo L.; ROOS, Claudine; RETIEF, Francois Pieter; MOOLMAN, Hans Jurie (Journal of Environmental Management and Tourism; Vol 14 No 7 (2023): JEMT, Volume XIV, Issue 7(71), Winter 2023DO - 10.14505/jemt.v14.7(71).06, 2023)
This paper evaluates the quality of environmental impact assessment (EIA) reports for lodge developments in Botswana’s Okavango Delta, which is a wetland of international importance and forms part of a transboundary conservation area and world heritage site. A quality review of 31 EIA reports, approved between 2013 and 2021, was conducted by applying a context specific EIA report quality review package. The review package consists of four review areas with seventeen categories and 64 sub-categories, adapted from similar international packages to address the specific legal requirements for EIA in Botswana as well as best practice.  Results show that the overall quality of the reports are poor, with 71% graded as ‘unsatisfactory’.  In general, descriptive areas of the EIA reports fared better, while the performance of the more analytical areas was ‘poor’.  Key areas of weakness include - the identification of impacts; prediction and assessment of impact magnitude; as well as identifying alternatives and mitigation measures. Overall results suggest that currently EIA report content is insufficient to inform decision-making towards sustainable tourism development in the Okavango Delta. It is recommended that areas of weakness can be addressed by providing clear strategic direction; developing a central data management system; setting norms and standards for tourism development as well as building capacity and awareness of key stakeholders. This will ensure that EIA remains a tool of choice for decision making and avoid becoming a mere ‘red-tape’/administrative process aimed at securing development approvals.